Justiça, caridade e compaixão na Metafísica da Ética de Schopenhauer - Bittencourt, Renato Nunes (2022)
In this article we analyze the statute of the compassion in the philosophy of Schopenhauer, and of that way such experience occurs in the practical action human being dis-charging in action jousts and charitables, by means of the understanding of the Metaphysical unit that involving all the human beings, stops beyond the proper phenomenics limitations of the beginning of individuation. We will still see implications of such perspective in the relation of the human being with the surrounding world, specifically in the treatment to the animals.